Measuring treatment response in children with autism spectrum disorder: Applications of the Brief Observation of Social Communication Change to the Autism Diagnostic Observation Schedule. (July 2019) - Kim, So Hyun; Grzadzinski, Rebecca; Martinez, Kassandra; Lord, Catherine
This study aims to determine the validity and reliability of applying the coding strategy from the Brief Observation of Social Communication Change, a newly validated treatment outcome measure, to videotaped segments of the Autism Diagnostic Observation Schedule. Results indicate strong reliability and validity of the Brief Observation of Social Communication Change ratings using the Autism Diagnostic Observation Schedule segments in detecting changes in social communication over the course of treatment in young, minimally verbal children with autism spectrum disorder. Results also suggest that the Brief Observation of Social Communication Change, when applied to Autism Diagnostic Observation Schedule segments, may be more sensitive in detecting subtle changes in social communication compared to the Autism Diagnostic Observation Schedule Calibrated Severity Scores. These results may support the application of the Brief Observation of Social Communication Change to pre-existing datasets of Autism Diagnostic Observation Schedule videos to examine treatment responses.